APOE epsilon4: a potential modulation factor in Rett syndrome - Zahorakova, Daniela; Jachymova, Marie; Kemlink, David; Baxova, Alice; Martasek, Pavel (Journal of child neurology, 2010)
Rett syndrome is a neurodevelopmental disorder mainly caused by de novo mutations in the MECP2 (methyl-CpG-binding protein 2) gene. There is considerable variation in the severity of clinical features among Rett syndrome patients, even among patients with the same MECP2 mutation. In addition to X-chromosome inactivation pattern, the genetic background of the affected individual might also have a role in determining the severity of the disorder. We suggest that APOE is one of the genetic modulating factors. We analyzed clinical phenotypes of 46 patients with Rett syndrome, with confirmed MECP2 mutation. We discovered that among epsilon4 carriers, some clinical features were more severe, and the developmental regression occurred 4 months earlier on average than in those without the epsilon4 allele. Earlier onset of regression suggests a possible trend; however, it did not achieve distinctive statistical significance. Nevertheless, the epsilon4 allele of APOE may serve as a candidate modulation factor for the Rett syndrome phenotype.
Keywords: apolipoprotein E4; Female; Heterozygote; protein 2 vázající methyl-CpG; Rett Syndrome; Alleles; Age of Onset; Apolipoprotein E4; Phenotype; předškolní dítě; Methyl-CpG-Binding Protein 2; heterozygot; Mutation; ženské pohlaví; kojenec; Rettův syndrom; stupeň závažnosti nemoci; věk při počátku nemoci; lidé; Humans; Severity of Illness Index; fenotyp; mutace; Child, Preschool; Infant; alely